Social Stigma, Family Support, and Healthcare Access as Determinants of Substance Use Among Transgender Populations: A Quantitative Study in South Sulawesi, Indonesia - Azwar, Muhammad; Widiastuty, Lilis; Setialaksana, Wirawan (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Substance abuse among transgender individuals remains underexplored, particularly in the context of how intersecting social determinants contribute to its prevalence. Existing studies often overlook the paradox wherein increased healthcare access does not equate to effective support due to systemic bias and exclusion in service provision. This study aims to analyze the influence of social stigma, family support, and healthcare access on drug abuse among transgender individuals in South Sulawesi. A cross-sectional quantitative study was conducted involving 230 transgender individuals in South Sulawesi, including 178 residing in Makassar. Data were collected through structured interviews and validated questionnaires, and then analyzed using descriptive statistics and logistic regression. The findings indicate that social stigma is a significant risk factor linked to an increased likelihood of substance use (p < 0.05), whereas family support shows a protective association, potentially mitigating the risk of substance use within this population. However, greater access to healthcare services is associated with higher chances of substance use, indicating challenges in the effectiveness of rehabilitation services for transgender individuals, particularly due to persistent stigma, lack of provider training in gender-sensitive care, and limited inclusivity within existing healthcare systems.These findings highlight the need for a holistic intervention framework that prioritizes stigma reduction, social support, and inclusive healthcare access, particularly within marginalized and rural health systems. The evidence may guide policies aimed at enhancing equity and responsiveness in service delivery for underserved populations.